Reliability and validity of sprint performance using the Alex7 motorized device - Skujyte, A.; Lukonaitiene, I.; Stanislovaitiene, J.; Šilinskas, V.; Bradauskiene, K.; Mamkus, G.; Kamandulis, S. (Frontiers in Sports and Active Living, 2024)
Introduction: Advancements in technology have recently made it possible to implement effective training solutions across different environmental conditions. This study evaluated the reliability and validity of measures obtained from the innovative motorized device, Alex7 (Inosportas, Lithuania), and differences in speed and kinematic characteristics between resisted and assisted sprinting in young football players.